2021
DOI: 10.1007/978-3-030-73100-7_73
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19’s (Mis)Information Ecosystem on Twitter: How Partisanship Boosts the Spread of Conspiracy Narratives on German Speaking Twitter

Abstract: In late 2019, the gravest pandemic in a century began spreading across the world. A state of uncertainty related to what has become known as SARS-CoV-2 has since fueled conspiracy narratives on social media about the origin, transmission and medical treatment of and vaccination against the resulting disease, COVID-19. Using social media intelligence to monitor and understand the proliferation of conspiracy narratives is one way to analyze the distribution of misinformation on the pandemic. We analyzed more tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 38 publications
(35 reference statements)
0
8
1
2
Order By: Relevance
“…The share of conspiracy tweets ranges from 0.6% to 18%. Shahrezaye et al (2020) analyze the spread of conspiracy theories in the German-language segment of Twitter. Shahrezaye et al (2020) found that less than 1% of 9.5 million COVID-19-related tweets are on the conspiracies.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The share of conspiracy tweets ranges from 0.6% to 18%. Shahrezaye et al (2020) analyze the spread of conspiracy theories in the German-language segment of Twitter. Shahrezaye et al (2020) found that less than 1% of 9.5 million COVID-19-related tweets are on the conspiracies.…”
Section: Literature Reviewmentioning
confidence: 99%
“… Shahrezaye et al (2020) analyze the spread of conspiracy theories in the German-language segment of Twitter. Shahrezaye et al (2020) found that less than 1% of 9.5 million COVID-19-related tweets are on the conspiracies. Out of about 4,900 tweets, Nuzhath et al (2020) identify about 18% as conspiracy theories.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Moreover, the use of the term by former US president Trump added a polemic meaning that is often used to discredit legacy news media (Quandt et al, 2019). The idea of fake news has also been employed to draw attention to the extensive spread of deceptive information in the form of misinformation, disinformation, hyperpartisan news, or conspiracy theories about the pandemic on social media platforms like Facebook, Twitter, YouTube, and Tiktok (Pennycook and Rand, 2021;Shahrezaye et al, 2021). In this study, when we use the term "fake news, " we refer to social media posts that make claims and put forward verifiably untrue speculations according to our analysis using a pre-trained BERT classifier.…”
Section: The Spread Of Misinformation and Its Antecedentsmentioning
confidence: 99%
“…Soziale Medien mit schwer kontrollierbarer Eigendynamik bieten Resonanzmöglichkeiten: Echoräume auf Internet, Facebook, Twitter, und viele andere. Diese können nicht nur zur beruhigenden Beziehungsarbeit in Zeiten des Lock-Down genutzt werden, sondern sind optimal geeignet, um krude Thesen zu kritikrefraktären Theorien auszubauen 14 21 22 . In der Trump-Ära „alternativer Fakten“ ist dafür der Boden bereitet 23 .…”
Section: Psychologische Und Andere Erklärungen Für Verschwörungstheorienunclassified
“…Eine aktuelle Analyse von fast 10 Millionen Tweets mit COVID-19-Bezug aus dem deutschen Sprachraum zeigte allerdings eher beruhigende Ergebnisse: Nur 0,6 % beinhalteten Hinweise auf Verschwörungstheorien 14 . Dabei ergaben sich Anhaltspunkte für eine größere Affinität von AfD-Anhängern zur Bill Gates-, 5G- oder Wuhan-Theorie, während Anhänger von SPD, Die Grünen und Die Linke häufiger auf die Segnungen der Homöopathie vertrauten 14 .…”
Section: Psychologische Und Andere Erklärungen Für Verschwörungstheorienunclassified